Pyrrolysyl-tRNA synthetase:tRNA(Pyl) structure reveals the molecular basis of orthogonality - Nozawa, Kayo (2008)
Pyrrolysine (Pyl), the 22(nd) natural amino acid, is genetically encoded by UAG and inserted into proteins by the unique suppressor tRNA(Pyl)1. The Methanosarcinaceae produce Pyl and express Pyl-containing methyltransferases that allow growth on methylamines2. Homologous methyltransferases and the Pyl biosynthetic and coding machinery are also found in two bacterial species1,3. Pyl coding is maintained by pyrrolysyl-tRNA synthetase (PylRS), which catalyzes the formation of Pyl-tRNA(Pyl)4,5. Pyl is not a recent addition to the genetic code. PylRS was already present in the last universal common ancestor6; it then persisted in organisms that utilize methylamines as energy sources. Recent protein engineering efforts added non-canonical amino acids to the genetic code7,8. This technology relies on the directed evolution of an ‘orthogonal’ tRNA synthetase:tRNA pair in which an engineered aminoacyl-tRNA synthetase (aaRS) specifically and exclusively acylates the orthogonal tRNA with a non-canonical amino acid. For Pyl the natural evolutionary process developed such a system some 3 billion years ago. When transformed into Escherichia coli, Methanosarcina barkeri PylRS and tRNA(Pyl) function as an orthogonal pair in vivo5,9. Here we demonstrate that Desulfitobacterium hafniense PylRS:tRNA(Pyl) is an orthogonal pair in vitro and in vivo, and present the crystal structure of this orthogonal pair. The ancient emergence of PylRS:tRNA(Pyl) allowed for the evolution of unique structural features in both the protein and the tRNA. These structural elements manifest an intricate, specialized aaRS:tRNA interaction surface highly distinct from those observed in any other known aaRS:tRNA complex; it is this general property that underlies the molecular basis of orthogonality.